PENERAPAN BERMAIN BALLIRET UNTUK MENINGKATKAN HASIL BELAJAR GERAK DASAR LONCAT PADA SISWA KELAS IV SEMESTER II SDN BUGEL02 KECAMATAN SIDOREJO KOTA SALATIGA TAHUN PELAJARAN 2012/2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the effectiveness of the game balliret in improving student learning outcomes Elementary School fourth grade second semester Bugel Sidorejo Salatiga District 02 Academic Year 2012/2013. This research is a classroom action research conducted by teachers in the class itself, takes place in two cycles involving all fourth grade students of SDN 02 Bugel totaling 14 students, consisting of 7 boys and 7 students daughters. Based on the results of this study illustrated that the implementation of the basic motion skip learning through play approach balliret showed success. Target mastery learning basic movement jump in the study was 85%. In the first cycle data showed that the percentage of 73.8% cognitive, affective aspects of 87.14%, and 68.28% of psychomotor aspects. So that the overall absorption of the material in the first cycle to 74% with an average of 73.8. Can be stated that in the first cycle of learning has not been successful. While in the second cycle the percentage of students in aspects of cognitive mastery reached 83.33%, reaching 100% affective aspects, and aspects of psychomotor reached 77.14%. You could say the percentage of mastery learning cycle II was 85% with an average of 85. It can be said that there is an increase in learning outcomes from the first cycle to the second cycle of 11.20%, ie from 73.8% to 85%. Thus, learning is said to have succeeded. Thus, it was concluded that the approach is effective balliret games improve learning outcomes of basic motion skip the second semester of fourth grade students of SDN 02 Bugel Sidorejo Salatiga District Academic Year 2012/2013.